Activities of the oral health teams in primary health care: a time-motion study - Lorrayne Belotti; Sofia Maito; Andrea Liliana Vesga-Varela; Leticia Yamawaka de Almeida; Maira Tamires da Silva; Ana Estela Haddad; Danielle da Costa Palacio; Daiana Bonfim (BMC, 2024)
Abstract Background Efficient planning of the oral health workforce in Primary Health Care (PHC) is paramount to ensure equitable community access to services. This requires a meticulous examination of the population's needs, strategic distribution of oral health professionals, and effective human resource management. In this context, the average time spent on care to meet the needs of users/families/communities is the central variable in healthcare professional workforce planning methods. However, many time measures are solely based on professional judgment or experience. Objective Calculate the average time parameters for the activities carried out by the oral health team in primary health care. Method This is a descriptive observational study using the time-motion method carried out in five Primary Health Care Units in the city of São Paulo, SP, Brazil. Direct and continuous observation of oral health team members occurred for 40 h spread over five days of a typical work week. Results A total of 696.05 h of observation were conducted with 12 Dentists, three Oral Health Assistants, and five Oral Health Technicians. The Dentists' main activity was consultation with an average duration of 24.39 min, which took up 42.36% of their working time, followed by documentation with 12.15%. Oral Health Assistants spent 31.57% of their time on infection control, while Oral Health Technicians spent 22.37% on documentation. Conclusion The study establishes time standards for the activities performed by the dental care team and provides support for the application of workforce planning methods that allow for review and optimization of the work process and public policies.